Pedagogical Competence of Teachers in Planning Vocational High School Learning - Ahyanuardi; Efronia, Yulia (LPPM Undiksha, 2022)
The teacher becomes the main actor in the learning process, especially in vocational education, namely productive learning which has its own characteristics that cannot be equated with adaptive and normative learning. This research aims to analyze directly the pedagogical evaluation of teachers in planning learning activities in vocational school in the field of electricity. This study used the Countenance Stake evaluation research method. This research focuses on one aspect, namely the planning aspect (antecedents) in the productive learning process. The research method used is the quantitative method. The data collection techniques used are questionnaires. Data analysis techniques are performed using descriptive quantitative. The results showed that there was a weakness in the pedagogical competence of teachers in making plans for learning activities with an average of 3.24 which was in the category quite well. Learning planning made by teachers has not been in accordance with process standards and also does not refer to a curriculum that is tailored to the abilities and needs of learners. There needs to be a review and improvement of the aspects that have not been fulfilled in the learning planning made by teachers and also the need to improve the pedagogical competence of teachers so that learning activities can be carried out properly and able to print competent vocational school graduates.